Our Illnesses - Anath Ariel de Vidas (Ateliers d'Anthropologie)
In the northern part of the Mexican state of Veracruz, the Teenek Indians believe that a certain illness afflicts only members of their own indigenous group. This assertion raises the question of the relation between emic ideas on affliction and ethnic identity. Examining the Teenek nosology and particularly the divination methods that the Teenek use to locate the origin of their particular misfortune, allows us not only to understand their etiology but also to analyze its symbolic structure. Through the myth of origin, this structure relates the concepts of disease prevalent in this group to their regional conflictual multiethnic context. Thus, Teenek pathology reveals not just a theory of causation but also expresses intra- and interethnic social tensions and gives insights into the question of an ethnotheoretical model of ethnicity.